Pedagogia de projetos na prevenção de doenças cardiovasculares - Duque, Mildren Lopes Wada (2015)
Cardiovascular diseases (CVD) are the leading cause of death in Brazil, being categorized as chronic diseases because they require ongoing management over a period of several years or decades. Therefore, early intervention on these risk factors is required. Objective: This study is an action research, which aims to analyze educational activities for the prevention of cardiovascular risk factors using as theoretical basis for projects in pedagogy of six teenagers in the study of an elementary school. Methods: After the educational intervention was carried out one guiding question to study participants. Two categories emerged from the Bardin content analysis: acquisition of knowledge about healthy habits and change in lifestyle. Results: The educational intervention using the pedagogy of projects allowed for study subjects to reflect on their way of life, helping to build new knowledge, awareness of their daily life and the prevention of cardiovascular risk factors. Conclusions: The pedagogy projects showed effectiveness in health education, however the lack of studies on it requires more research is done.